2022
DOI: 10.21511/ppm.20(4).2022.26
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between logistics and information and communication technologies and their impact on the economy of Kazakhstan

Abstract: This study aims to analyze the impact of logistics and information and communication technologies (ICT) on Kazakhstan’s economic growth, which requires rethinking search and management tools. The study used the methods of descriptive data statistics, checking the data for the normality of the distribution, and Spearman’s correlation analysis. The information database comprised the National Bank, the World Development Bank, and the national statistics of the Agency for Strategic Planning and Reforms of the Repu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…This is an interesting topic to explore and has been covered in a number of academic fields. A review of the literature has shown that ICT in the logistics industry has a significant impact on economic development [4]. The automation and digitalization of logistics processes of different nature concerns both fullfilment centres and classic logistics warehouses and distribution centres.…”
Section: Introductionmentioning
confidence: 99%
“…This is an interesting topic to explore and has been covered in a number of academic fields. A review of the literature has shown that ICT in the logistics industry has a significant impact on economic development [4]. The automation and digitalization of logistics processes of different nature concerns both fullfilment centres and classic logistics warehouses and distribution centres.…”
Section: Introductionmentioning
confidence: 99%
“…Transport is becoming more and more energy saving and "green", safe for the passenger and the environment. Many countries around the world are already replacing cars with internal combustion engines with electric cars (Mykytenko & Drachuk, 2023;Amri et al, 2022;Kredina et al, 2022). The main trend of all vehicles is the speed and economy increase.…”
mentioning
confidence: 99%